2018
DOI: 10.1007/s13340-018-0355-1
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted magnetic resonance imaging in the pancreas of fulminant type 1 diabetes

Abstract: Abrupt disease onset and severe metabolic disorders are main characteristics of fulminant type 1 diabetes. Diffusionweighted magnetic resonance imaging (DWI) is an imaging technique that reflects restricted diffusion in organs and can detect mononuclear cell infiltration into the pancreas at the onset of the disease. Fourteen patients with fulminant type 1 diabetes who underwent abdominal magnetic resonance imaging were recruited for the measurement of apparent diffusion coefficient (ADC) values of the pancrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
2
2
0
Order By: Relevance
“…MRI revealed that the size of the pancreas did not change between Days 8 and 50 after the onset. However, MRI showed higher ADC values at Day 50 than at Day 8, which corroborated with the results of previous studies on fulminant type 1 diabetes 14 …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…MRI revealed that the size of the pancreas did not change between Days 8 and 50 after the onset. However, MRI showed higher ADC values at Day 50 than at Day 8, which corroborated with the results of previous studies on fulminant type 1 diabetes 14 …”
Section: Discussionsupporting
confidence: 91%
“…Oikawa et al showed a negative correlation between time from the onset of premonitory symptoms to diagnosis and anti-GAD antibody levels in GAD-positive fulminant type 1 diabetes. 13 The patient in the present study showed more rapid onset of GAD-positive fulminant type 1 diabetes (4.4 days earlier than that in the national survey results) 6 and was hospitalized approximately 24 h after the onset of premonitory symptoms. Nevertheless, GAD antibodies remained moderately positive (44.6 IU/L), and the results were not consistent with those of previous studies.…”
Section: T a B L Esupporting
confidence: 37%
See 2 more Smart Citations